Oral Presentations Abstracts: ETHICS, DATA AND INFORMATION IN GENOME SEQUENCING IN NEWBORNS - LORENZO, David; ESQUERDA, Montserrat; BOFARULL, Margarita; PALAU, Francesc; ORDOÑEZ, Jose Javier; CUSI, Victoria; CAMBRA, Francisco J.; ILLA, Marc; CARRERA, Joan (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 One of the current debates in Genetics is the genomic sequencing in newborns. Thanks to the genomic technologies, it is currently possible to detect diseases that a newborn may suffer in the short, medium or long term. Genomic tests pose some important ethical issues. Those issues can be classified in three different types: those regarding the object of the screening (genes that must be analyzed), those related to the information (how it must be managed) and those regarding justice questions (economic costs, population to be included in some screening programs). This study is based on a previous study whose aim was to present a general view of those three ethical problems. This study aims to focus on one of these three problems: the information. We think that how to manage the information on the results of a genomic sequencing in newborns is perhaps the most important ethical issue in this topic. Hence this work aims to address these questions regarding information on genomic sequencing: How the genomic screening has to be explained to the parents in order to get the informed consent? Should the physician give them all the data or only the information related to some genes about which he is sure that they will cause a disease? How the genomic information has to be managed? Can we keep this information once we have finished the screening of a newborn? Should we destroy it after the screening? Is it ethical that parents, without a prescription or medical control, can do on their own a genomic screening on their newborn child?